2022
DOI: 10.1530/eje-22-0104
|View full text |Cite
|
Sign up to set email alerts
|

Higher premorbid serum testosterone predicts COVID-19-related mortality risk in men

Abstract: Objective Men are at greater risk from COVID-19 than women. Older, overweight men, and those with type 2 diabetes, have lower testosterone concentrations, and poorer COVID-19-related outcomes. We analysed associations of premorbid serum testosterone concentrations, not confounded by effects of acute SARS-CoV-2 infection, with COVID-19-related mortality risk in men. Design UK Biobank prospective cohort study of community-dwelling men aged 40-69 years. Methods Serum total testosterone and sex hormone-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Since testosterone is not measured on a regular basis in all persons unlike other clinical lab test, it is hard to find studies that measured testosterone before COVID-19, additionally testosterone measured during or after COVID-19 is not as accurate for assessing the relation between testosterone level and COVID-19 severity and mortality, because during COVID-19 infection or even long after COVID-19 (even after 3 months) testosterone levels are affected due to detrimental effects of SARS-CoV-2 infection on leydig cells; testosterone post-COVID levels cannot be considered as accurate as pre-COVID due to absence of post-COVID testosterone levels of persons who died as well. one study that dosed testosterone before COVID-19 showed a direct relationship between testosterone level and COVID-19 severity as well as mortality (39). Still, testosterone is not necessarily the major determinant of androgens in terms of prediction of COVID-19 severity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Since testosterone is not measured on a regular basis in all persons unlike other clinical lab test, it is hard to find studies that measured testosterone before COVID-19, additionally testosterone measured during or after COVID-19 is not as accurate for assessing the relation between testosterone level and COVID-19 severity and mortality, because during COVID-19 infection or even long after COVID-19 (even after 3 months) testosterone levels are affected due to detrimental effects of SARS-CoV-2 infection on leydig cells; testosterone post-COVID levels cannot be considered as accurate as pre-COVID due to absence of post-COVID testosterone levels of persons who died as well. one study that dosed testosterone before COVID-19 showed a direct relationship between testosterone level and COVID-19 severity as well as mortality (39). Still, testosterone is not necessarily the major determinant of androgens in terms of prediction of COVID-19 severity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Testosterone post-COVID levels cannot be considered as accurate as pre-COVID due to absence of post-COVID testosterone levels of persons who died as well. One study that dosed testosterone before COVID-19 showed a direct relationship between testosterone level and COVID-19 severity as well as mortality [39]. still, testosterone is not necessarily the major determinant of androgens in terms of prediction of COVID-19 severity.…”
Section: Androgens' Role In Ace2 and Tmprss2 Expression Regulation As...mentioning
confidence: 99%
“… 69 Conversely, in community‐dwelling men aged 40–69 years, serum total testosterone measured years prior to any exposure to SARS‐CoV‐2 a U‐shaped association of total testosterone with risk of death from Covid‐19 was apparent. 70 Interestingly, when the model was adjusted for additional covariates including multiple lifestyle and demographic variables, blood cholesterol, and prevalent medical conditions, Testosterone levels were positively correlated with risk of dying from Covid‐19. 70 This suggests that potential beneficial effects of testosterone may occur only via influence on the presence of medical comorbidities including obesity and type 2 diabetes which are known to increase Covid‐19 severity.…”
Section: Testosterone and Covid‐19 Severitymentioning
confidence: 98%
“… 70 Interestingly, when the model was adjusted for additional covariates including multiple lifestyle and demographic variables, blood cholesterol, and prevalent medical conditions, Testosterone levels were positively correlated with risk of dying from Covid‐19. 70 This suggests that potential beneficial effects of testosterone may occur only via influence on the presence of medical comorbidities including obesity and type 2 diabetes which are known to increase Covid‐19 severity. However, the significance of this relationship is diminished by the testosterone assessment taking place years prior to Covid‐19 infection, and therefore may not reflect the man's T level at time of pandemic.…”
Section: Testosterone and Covid‐19 Severitymentioning
confidence: 98%
“…Testosterone can affect the entry of SARS-CoV-2 by promoting expression of ACE2 and TMPRSS2 via androgen receptor a Kalidhindi et al 8 Men with low testosterone exhibit higher concentrations of pro-inflammatory cytokines during Covid-19 b Dhindsa et al 9 Rastrelli et al 10 Çayan et al 11 Pre-existing male hypogonadism is a risk factor for Covid b Dhindsa et al 4 Yeap et al 12 Testosterone therapy protects against Covid severity b Dhindsa et al 4 Baillargeon et al 13 Androgen deprivation therapies protect against Covid-19 a Montopoli et al 7 Klein et al 14 Welén et al 15 Nickols et al 16 Abbreaviations: ACE2, angiotensin-converting enzyme 2; Covid-19, Coronavirus disease 2019; SARS-CoV-2, severe acute respiratory syndrome 2 coronavirus; TMPRSS2, transmembrane serine protease 2.…”
Section: Supporting Studies Nonsupporting Studiesmentioning
confidence: 99%